Secondary battery

The use of a ternary copolymer binder in the negative electrode of a secondary battery, with controlled carbon, nitrogen, and lithium ratios, addresses performance gaps by enhancing efficiency and stability, leading to improved battery characteristics.

JP2025005812APending Publication Date: 2025-01-17MURATA MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023106191
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing secondary batteries do not achieve optimal battery characteristics, necessitating improvements in performance.

Method used

A secondary battery design incorporating a negative electrode with a binder composed of a ternary copolymer of acrylamide, lithium acrylate, and acrylonitrile, where specific concentration ratios of carbon, nitrogen, and lithium are maintained through X-ray photoelectron spectroscopy analysis, optimizing the negative electrode's surface composition.

Benefits of technology

This configuration enhances the lithium input/output efficiency, reduces irreversible capacity, and maintains low internal resistance, resulting in improved battery characteristics and stability over repeated charging and discharging cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005812000001_ABST
    Figure 2025005812000001_ABST
Patent Text Reader

Abstract

To provide a secondary battery that can obtain excellent battery characteristics.SOLUTION: A secondary battery includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode active material layer containing a negative electrode binder and a coating provided on the surface of the negative electrode active material layer, and the negative electrode binder contains a copolymer of acrylamide, lithium acrylate, and acrylonitrile. A C1s spectrum, an N1s spectrum, and an Li1s spectrum are detected by surface analysis of the negative electrode using X-ray photoelectron spectroscopy, and a first concentration ratio calculated by formula (1) is 0.4 or more and 2.7 or less, and a second concentration ratio calculated by formula (2) is 3.4 or more and 5.9 or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to a secondary battery. [Background technology]

[0002] Due to the widespread use of various electronic devices such as mobile phones, secondary batteries have been developed as power sources that are small and lightweight and can provide high energy density. These secondary batteries include a positive electrode, a negative electrode, and an electrolyte solution, and various studies have been conducted on the configuration of the secondary battery.

[0003] Specifically, the electrode contains a material having an imide bond or an amide bond, and the surface of the electrode is analyzed using X-ray photoelectron spectroscopy (see, for example, Patent Documents 1 to 7). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-037842 A [Patent Document 2] JP 2017-195231 A [Patent Document 3] JP 2018-195434 A [Patent Document 4] JP 2005-203370 A [Patent Document 5] JP 2007-080827 A [Patent Document 6] JP 2020-087777 A [Patent Document 7] China Patent Application Publication No. 111139002 Summary of the Invention [Problem to be solved by the invention]

[0005] Various studies have been conducted to improve the battery characteristics of secondary batteries, but the battery characteristics are still insufficient and there is room for improvement.

[0006] The present technology has been made in view of such problems, and an object of the technology is to provide a secondary battery that is capable of obtaining excellent battery characteristics. [Means for solving the problem]

[0007] A secondary battery according to an embodiment of the present technology includes a positive electrode, a negative electrode, and an electrolyte. The negative electrode includes a negative electrode active material layer containing a negative electrode binder, and a coating film provided on the surface of the negative electrode active material layer, and the negative electrode binder includes a copolymer of acrylamide, lithium acrylate, and acrylonitrile. A C1s spectrum, an N1s spectrum, and an Li1s spectrum are detected by surface analysis of the negative electrode using X-ray photoelectron spectroscopy, and a first concentration ratio calculated by formula (1) is 0.4 or more and 2.7 or less, and a second concentration ratio calculated by formula (2) is 3.4 or more and 5.9 or less.

[0008] X1 = XC / XN (1) (X1 is the first concentration ratio. XC is the atomic concentration (atomic %) of carbon calculated based on the C1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.)

[0009] X2=XL / XN (2) (X2 is the second concentration ratio. XL is the atomic concentration (atomic %) of lithium calculated based on the Li1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.)

[0010] Here, the C1s spectrum is a spectrum having a peak top within the binding energy range of 282.0 eV to 283.6 eV in the detection results of the C1s spectrum originating from carbon (the horizontal axis is binding energy (eV) and the vertical axis is spectral intensity (arbitrary units)).

[0011] The N1s spectrum is a spectrum having a peak top within the binding energy range of 394.5 eV to 405.0 eV in the detection results of the N1s spectrum originating from nitrogen (the horizontal axis is binding energy (eV) and the vertical axis is spectral intensity (arbitrary units)).

[0012] Furthermore, the Li1s spectrum is a spectrum having a peak top within the binding energy range of 50.0 eV to 61.5 eV in the detection results of the Lis spectrum derived from lithium (the horizontal axis is binding energy (eV) and the vertical axis is spectral intensity (arbitrary units)).

[0013] Details of the analysis procedure for the surface analysis of the negative electrode using X-ray photoelectron spectroscopy and the calculation procedures for the first concentration ratio and the second concentration ratio (including the calculation procedures for the atomic concentrations XC, XN, and XL) will be described later. Effect of the Invention

[0014] According to a secondary battery of one embodiment of the present technology, the negative electrode includes a negative electrode active material layer and a coating, the negative electrode active material layer includes a negative electrode binder, and the negative electrode binder includes a copolymer of acrylamide, lithium acrylate, and acrylonitrile. In a surface analysis of the positive electrode using X-ray photoelectron spectroscopy, the first concentration ratio is 0.4 or more and 2.7 or less, and the second concentration ratio is 3.4 or more and 5.9 or less, so that excellent battery characteristics can be obtained.

[0015] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a cross-sectional view illustrating a configuration of a secondary battery according to an embodiment of the present technology. [Diagram 2] FIG. 2 is a cross-sectional view illustrating the configuration of the battery element shown in FIG. [Diagram 3] FIG. 3 is a plan view showing the configuration of each of the positive electrode and the negative electrode shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Secondary battery 1-1.Configuration 1-2.Physical properties 1-3.Operation 1-4. Manufacturing method 1-5. Actions and Effects 2. Variations 3. Uses of secondary batteries

[0018] <1. Secondary battery> First, a secondary battery according to an embodiment of the present technology will be described.

[0019] The secondary battery described here is a secondary battery in which battery capacity is obtained by utilizing the absorption and release of an electrode reactant, and is provided with a positive electrode, a negative electrode, and an electrolyte.

[0020] The charge capacity of the negative electrode is preferably larger than the discharge capacity of the positive electrode. That is, the electrochemical capacity per unit area of ​​the negative electrode is preferably larger than the electrochemical capacity per unit area of ​​the positive electrode. This is to prevent deposition of an electrode reactant on the surface of the negative electrode during charging.

[0021] The type of the electrode reactant is not particularly limited, but specifically, it is a light metal such as an alkali metal or an alkaline earth metal. Specific examples of the alkali metal include lithium, sodium, and potassium, and specific examples of the alkaline earth metal include beryllium, magnesium, and calcium.

[0022] In the following, an example will be given in which the electrode reactant is lithium. A secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In this lithium ion secondary battery, lithium is absorbed and released in an ionic state.

[0023] <1-1. Configuration> Fig. 1 shows a cross-sectional configuration of a secondary battery. Fig. 2 shows a cross-sectional configuration of a battery element 20 shown in Fig. 1. Fig. 3 shows the planar configurations of a positive electrode 21 and a negative electrode 22 shown in Fig. 2.

[0024] However, Fig. 2 shows only a part of the battery element 20. Fig. 3 shows a state in which the positive electrode 21 and the negative electrode 22 are not wound.

[0025] As shown in FIGS. 1 and 2, this secondary battery mainly includes a battery can 11, a pair of insulating plates 12, 13, a battery element 20, a positive electrode lead 25, and a negative electrode lead .

[0026] The secondary battery described here has a battery element 20 housed in a cylindrical battery can 11, and is therefore a so-called cylindrical secondary battery.

[0027] [Battery can] As shown in FIG. 1, the battery can 11 is a storage member that stores the battery element 20 and the like. The battery can 11 has one open end and the other closed end, and thus has a hollow structure. The battery can 11 contains one or more types of metal materials such as iron, aluminum, iron alloy, and aluminum alloy. The surface of the battery can 11 may be plated with a metal material such as nickel.

[0028] At one open end of the battery can 11, a battery lid 14, a safety valve mechanism 15, and a PTC element 16, which is a thermal resistor element, are crimped via a gasket 17. Thus, the battery can 11 is sealed by the battery lid 14. Here, the battery lid 14 contains the same material as the material from which the battery can 11 is formed. The safety valve mechanism 15 and the PTC element 16 are each provided on the inside of the battery lid 14, and the safety valve mechanism 15 is electrically connected to the battery lid 14 via the PTC element 16. The gasket 17 contains an insulating material, and the surface of the gasket 17 may be coated with asphalt or the like.

[0029] In this safety valve mechanism 15, when the internal pressure of the battery can 11 reaches a certain level due to factors such as an internal short circuit or external heating, the disk plate 15A reverses, cutting off the electrical connection between the battery lid 14 and the battery element 20. To prevent abnormal heat generation due to a large current, the electrical resistance of the PTC element 16 increases with increasing temperature.

[0030] [Insulating plate] 1, the insulating plates 12 and 13 are disposed so as to face each other across the battery element 20. As a result, the battery element 20 is sandwiched between the insulating plates 12 and 13.

[0031] [Battery element] The battery element 20 is housed in a battery can 11. The battery element 20 is a so-called power generating element, and includes a positive electrode 21, a negative electrode 22, a separator 23, and an electrolyte (not shown), as shown in Figs. 1 and 2.

[0032] Here, the battery element 20 is a so-called wound electrode body. That is, the positive electrode 21 and the negative electrode 22 are stacked on each other with a separator 23 interposed therebetween, and are wound while facing each other with the separator 23 interposed therebetween. A center pin 24 is inserted into a space 20S provided at the winding center of the battery element 20. However, the center pin 24 may be omitted.

[0033] (positive electrode) As shown in FIG. 2, the positive electrode 21 includes a positive electrode current collector 21A and a positive electrode active material layer 21B.

[0034] The positive electrode current collector 21A has a pair of surfaces on which the positive electrode active material layer 21B is provided. The positive electrode current collector 21A contains a conductive material such as a metal material, and a specific example of the conductive material is aluminum.

[0035] The positive electrode active material layer 21B contains one or more types of positive electrode active materials that absorb and release lithium. However, the positive electrode active material layer 21B may further contain one or more types of other materials such as a positive electrode binder and a positive electrode conductive agent. The method of forming the positive electrode active material layer 21B is not particularly limited, but specifically includes a coating method.

[0036] Here, the positive electrode active material layer 21B is provided on both sides of the positive electrode current collector 21A. However, the positive electrode active material layer 21B may be provided on only one side of the positive electrode current collector 21A on the side where the positive electrode 21 faces the negative electrode 22.

[0037] The type of the positive electrode active material is not particularly limited, but specifically, it is a lithium-containing compound, etc. This is because a high voltage can be obtained. This lithium-containing compound is a compound containing lithium and one or more transition metal elements as constituent elements, and may further contain one or more other elements (excluding lithium and transition metal elements) as constituent elements. The type of the other elements is not particularly limited, but specifically, it is an element belonging to Groups 2 to 15 of the long periodic table. The type of the lithium-containing compound is not particularly limited, but specifically, it is an oxide, a phosphate compound, a silicate compound, a borate compound, etc.

[0038] Specific examples of oxides are LiNiO2, LiCoO2, LiCo 0.98 Al 0.01 Mg 0.01 O2, LiNi 0.82 Co 0.14 Al 0.04 O2, LiNi0.5 Co 0.2 Mn 0.3 Specific examples of phosphate compounds include LiFePO4, LiMnPO4 and LiFe 0.5 Mn 0.5 PO4, etc.

[0039] The positive electrode binder contains one or more of materials such as synthetic rubber and polymer compounds. Specific examples of synthetic rubber include styrene butadiene rubber, fluorine-based rubber, and ethylene propylene diene. Specific examples of polymer compounds include polyvinylidene fluoride, polyimide, and carboxymethyl cellulose.

[0040] The positive electrode conductive agent contains one or more conductive materials such as a carbon material, a metal material, and a conductive polymer compound. Specific examples of the carbon material include graphite, carbon black, acetylene black, and ketjen black.

[0041] 3, the positive electrode active material layer 21B is provided on a portion of the surface of the positive electrode current collector 21A, more specifically, in a central region in the longitudinal direction (the left-right direction in FIG. 3) of the positive electrode current collector 21A. In FIG. 3, the positive electrode active material layer 21B is shaded.

[0042] (Negative electrode) As shown in FIG. 2, the negative electrode 22 includes a negative electrode current collector 22A, a negative electrode active material layer 22B, and a coating 22C.

[0043] The negative electrode current collector 22A has a pair of surfaces on which the negative electrode active material layer 22B is provided. The negative electrode current collector 22A contains a conductive material such as a metal material, and a specific example of the conductive material is copper.

[0044] The negative electrode active material layer 22B contains a negative electrode active material and a negative electrode binder. However, the negative electrode active material layer 22B may further contain one or more of other materials such as a negative electrode conductive agent. The method for forming the negative electrode active material layer 22B is not particularly limited, but specifically includes a coating method.

[0045] Here, the negative electrode active material layer 22B is provided on both sides of the negative electrode current collector 22A. However, the negative electrode active material layer 22B may be provided on only one side of the negative electrode current collector 22A on the side where the negative electrode 22 faces the positive electrode 21.

[0046] The negative electrode active material is a material that absorbs and releases lithium. The type of the negative electrode active material is not particularly limited, but specifically, it is one or more of materials such as carbon materials and metal-based materials. This is because a high energy density can be obtained.

[0047] Specific examples of the carbon material include graphitizable carbon, non-graphitizable carbon, graphite, etc. The graphite may be natural graphite, artificial graphite, or both.

[0048] Metallic materials are a general term for materials that contain one or more of the metallic elements and semi-metallic elements that can form an alloy with lithium as constituent elements, and specific examples of the metallic elements and semi-metallic elements include silicon and tin. The metallic materials may be a single element, an alloy, a compound, a mixture of two or more of these, or a material that contains two or more of these phases. Specific examples of metallic materials are TiSi2 and SiO x (0 <x≦2または0.2<x<1.4)などである。

[0049] The surface of the metal-based material may be partially or entirely covered with a carbon material, the details of which are as described above.

[0050] The negative electrode binder is a substance that binds together materials such as the negative electrode active material, and contains a ternary copolymer, which is a polymer compound.

[0051] This ternary copolymer is a copolymer containing three types of elements, nitrogen (N), carbon (C), and lithium (Li), as its constituent elements, and more specifically, is a copolymer of acrylamide, lithium acrylate, and acrylonitrile.

[0052] Acrylamide contains a nitrogen-containing group (-C(=O)-NH2), so it contains carbon and nitrogen as constituent elements. Lithium acrylate contains a lithium-containing group (-C(=O)-OLi), so it contains carbon and lithium as constituent elements. Acrylonitrile contains a nitrogen-containing group (-CN), so it contains carbon and nitrogen as constituent elements. As a result, terpolymers contain carbon, nitrogen, and lithium as constituent elements.

[0053] The copolymerization amounts of acrylamide, lithium acrylate, and acrylonitrile in the ternary copolymer are not particularly limited and can be set arbitrarily.

[0054] The reason why the negative electrode binder contains a ternary copolymer is that, as described later, the negative electrode binder decomposes, reacts, and dissolves during the manufacturing process of the secondary battery (the stabilization process of the secondary battery after assembly), forming the coating 22C containing carbon, nitrogen, and lithium as constituent elements. Thus, the negative electrode binder containing a ternary copolymer is a supply source of carbon, nitrogen, and lithium contained as constituent elements in the coating 22C.

[0055] The ternary copolymer may further contain a copolymer of acrylamide, acrylic acid, and acrylonitrile, or may contain a copolymer of acrylamide, acrylic acid, lithium acrylate, and acrylonitrile, or may contain both. Since this acrylic acid contains a carboxyl group (-C(=O)-OH), it contains carbon as a constituent element but does not contain lithium as a constituent element.

[0056] The copolymerization amount of acrylic acid in the ternary copolymer is not particularly limited. In particular, the copolymerization amount of acrylic acid in the ternary copolymer is preferably sufficiently smaller than the copolymerization amounts of acrylamide, lithium acrylate, and acrylonitrile in the ternary copolymer. This is to ensure the supply amount of lithium contained as a constituent element in the coating 22C.

[0057] The negative electrode binder may further contain one or more of other polymer compounds (excluding ternary copolymers) as necessary. The other polymer compounds include one or more of materials such as synthetic rubber and polymer compounds. The details of the synthetic rubber and polymer compounds are as described above.

[0058] The negative electrode conductive agent is a substance that improves the conductivity of the negative electrode active material layer 22B, and details regarding the negative electrode conductive agent are the same as those regarding the positive electrode conductive agent.

[0059] Among them, it is preferable that the negative electrode conductive agent contains a carbon material, because the carbon material functions not only as a negative electrode conductive agent but also as a negative electrode active material, thereby improving the conductivity of the negative electrode active material layer 22B and also improving the lithium absorption / release property of the negative electrode active material layer 22B.

[0060] The coating 22C is provided on the surface of the negative electrode active material layer 22B, and therefore covers the surface of the negative electrode active material layer 22B.

[0061] Here, the coating 22C covers the entire surface of the negative electrode active material layer 22B. However, the coating 22C may cover only a portion of the surface of the negative electrode active material layer 22B. In this case, a plurality of coatings 22C separated from one another may cover the surface of the negative electrode active material layer 22B.

[0062] As described above, the coating 22C is formed on the surface of the negative electrode active material layer 22B by stabilizing the secondary battery after assembly, and contains carbon, nitrogen, and lithium derived from the ternary copolymer that is the negative electrode binder as constituent elements. The composition of the coating 22C is not particularly limited as long as it contains carbon, nitrogen, and lithium as constituent elements.

[0063] The thickness of the coating 22C is not particularly limited and can be set arbitrarily. In particular, the thickness of the coating 22C is preferably sufficiently small, more specifically, 10 nm or less. This is because the thickness of the coating 22C is not too large, so that the internal resistance of the negative electrode 22 is prevented from increasing too much, and the lithium absorption / release property of the negative electrode active material layer 22B is also prevented from decreasing too much.

[0064] Here, as shown in Fig. 3, the negative electrode active material layer 22B is provided on the entire surface of the negative electrode current collector 22A, more specifically, on the entire region in the longitudinal direction (the left-right direction in Fig. 3) of the negative electrode current collector 22A. As a result, the coating 22C is provided on the entire region in the longitudinal direction of the negative electrode current collector 22A, similar to the negative electrode active material layer 22B. In Fig. 3, the coating 22C is shaded.

[0065] Thus, the negative electrode 22 includes one facing portion R1 and two non-facing portions R2. The facing portion R1 is a portion involved in the charge / discharge reaction because the negative electrode active material layer 22B faces the positive electrode active material layer 21B. In contrast, the non-facing portion R2 is a portion that is not substantially involved in the charge / discharge reaction because the negative electrode active material layer 22B does not face the positive electrode active material layer 21B. Here, the facing portion R1 is disposed between the two non-facing portions R2.

[0066] In this secondary battery, in order to improve the battery characteristics, the negative electrode 22 (coating 22C) satisfies certain conditions regarding the physical properties thereof. The physical properties of the negative electrode 22 will be described in detail later.

[0067] (Separator) 2, the separator 23 is an insulating porous film interposed between the positive electrode 21 and the negative electrode 22, and allows lithium to pass through in an ion state while preventing the occurrence of a short circuit due to contact between the positive electrode 21 and the negative electrode 22. The separator 23 contains a polymer compound such as polyethylene.

[0068] (electrolyte) The electrolytic solution is a liquid electrolyte, and is impregnated into each of the positive electrode 21, the negative electrode 22, and the separator 23. The electrolytic solution contains a solvent and an electrolyte salt.

[0069] The solvent contains one or more types of non-aqueous solvents (organic solvents), and the electrolyte containing the non-aqueous solvent is a so-called non-aqueous electrolyte.

[0070] The non-aqueous solvent is an ester or an ether, more specifically, a carbonate compound, a carboxylate compound, a lactone compound, etc. This is because the dissociation property of the electrolyte salt and the mobility of the ions are improved.

[0071] The carbonate ester compounds are cyclic carbonate esters and chain carbonate esters. Specific examples of the cyclic carbonate esters are ethylene carbonate and propylene carbonate, and specific examples of the chain carbonate esters are dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0072] The carboxylate compound is a chain carboxylate, etc. Specific examples of the chain carboxylate are ethyl acetate, ethyl propionate, propyl propionate, and ethyl trimethylacetate.

[0073] The lactone compound is lactone, etc. Specific examples of lactone are γ-butyrolactone and γ-valerolactone, etc.

[0074] The ethers may be 1,2-dimethoxyethane, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, or the like.

[0075] The non-aqueous solvent is, for example, an unsaturated cyclic carbonate, a fluorinated cyclic carbonate, a sulfonate, a phosphate, an acid anhydride, a nitrile compound, or an isocyanate compound, because the electrochemical stability of the electrolyte is improved.

[0076] Specific examples of unsaturated cyclic carbonates include vinylene carbonate, vinylethylene carbonate, and methyleneethylene carbonate. Specific examples of fluorinated cyclic carbonates include monofluoroethylene carbonate and difluoroethylene carbonate. Specific examples of sulfonic acid esters include propane sultone and propene sultone. Specific examples of phosphate esters include trimethyl phosphate and triethyl phosphate. Specific examples of acid anhydrides include succinic anhydride, 1,2-ethanedisulfonic anhydride, and 2-sulfobenzoic anhydride. Specific examples of nitrile compounds include succinonitrile. Specific examples of isocyanate compounds include hexamethylene diisocyanate.

[0077] The electrolyte salt contains one or more kinds of light metal salts such as lithium salts.

[0078] Specific examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (LiN(FSO2)2), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium tris(trifluoromethanesulfonyl)methide (LiC(CF3SO2)3), lithium bis(oxalato)borate (LiB(C2O4)2), lithium monofluorophosphate (Li2PFO3), and lithium difluorophosphate (LiPF2O2). This is because high battery capacity can be obtained.

[0079] The content of the electrolyte salt is not particularly limited, but specifically, it is 0.3 mol / kg to 3.0 mol / kg relative to the solvent, because high ionic conductivity can be obtained.

[0080] [Positive and negative leads] 1 and 2, the positive electrode lead 25 is connected to the positive electrode current collector 21A of the positive electrode 21, and contains a conductive material such as aluminum. The positive electrode lead 25 is electrically connected to the battery lid 14 via the safety valve mechanism 15.

[0081] 1 and 2, the negative electrode lead 26 is connected to the negative electrode current collector 22A of the negative electrode 22, and contains a conductive material such as nickel. The negative electrode lead 26 is electrically connected to the battery can 11.

[0082] <1-2.Physical properties> As described above, in this secondary battery, predetermined conditions are met regarding the physical properties of the negative electrode 22 in order to improve the battery characteristics.

[0083] [Physical property conditions] Specifically, the results of the analysis of the surface of the negative electrode 22 using X-ray photoelectron spectroscopy (XPS), i.e., the results of the analysis of the coating 22C present on the outermost surface of the negative electrode 22, satisfy the two conditions (physical property conditions 1 and 2) described below.

[0084] As described above, the coating 22C contains carbon, nitrogen, and lithium as its constituent elements, and therefore, by performing surface analysis of the coating 22C using XPS, three types of XPS spectra are detected: a carbon spectrum (C1s spectrum), a nitrogen spectrum (N1s spectrum), and a lithium spectrum (Li1s spectrum).

[0085] In the surface analysis of the coating 22C using XPS, one or more of other spectra other than the above-mentioned three types of XPS spectra may be detected. Specific examples of other spectra include a fluorine spectrum (F1s spectrum), an oxygen spectrum (O1s spectrum), a boron spectrum (B1s spectrum), a phosphorus spectrum (P2p spectrum), and a silicon spectrum (Si2p spectrum).

[0086] In this surface analysis, all atoms contained in the coating 22C are analyzed in a region between the surface of the coating 22C and a depth of 10 nm from the surface of the coating 22C, thereby detecting the C1s spectrum, the N1s spectrum, and the L1s spectrum, as described above.

[0087] The C1s spectrum is an XPS spectrum derived from carbon (carbon atoms) contained in the coating 22C. The N1s spectrum is an XPS spectrum derived from nitrogen (nitrogen atoms) contained in the coating 22C. The Li1s spectrum is an XPS spectrum derived from lithium (lithium atoms) contained in the coating 22C.

[0088] Here, the C1s spectrum is a spectrum having a peak top within the binding energy range of 279.0 eV to 296.5 eV in the detection results of the C1s spectrum originating from carbon (the horizontal axis is binding energy (eV) and the vertical axis is spectral intensity (arbitrary units)).

[0089] When a plurality of peaks are present in the detection result of the C1s spectrum, as described above, the spectrum having a peak top within the binding energy range of 282.0 eV to 283.6 eV is regarded as the C1s spectrum.

[0090] The N1s spectrum is a spectrum having a peak top within the binding energy range of 394.0 eV to 408.0 eV in the detection results of the N1s spectrum originating from nitrogen (the horizontal axis is binding energy (eV) and the vertical axis is spectral intensity (arbitrary units)).

[0091] When a plurality of peaks are present in the detection result of the N1s spectrum, as described above, the spectrum having a peak top within the binding energy range of 394.5 eV to 405.0 eV is regarded as the N1s spectrum.

[0092] Furthermore, the Li1s spectrum is a spectrum having a peak top within the binding energy range of 50.0 eV to 63.0 eV in the detection results of the Li1s spectrum derived from lithium (the horizontal axis is binding energy (eV) and the vertical axis is spectral intensity (arbitrary units)).

[0093] When a plurality of peaks are present in the detection result of the Li1s spectrum, the spectrum having a peak top within the binding energy range of 50.0 eV to 61.5 eV is regarded as the Li1s spectrum.

[0094] This allows the atomic concentration (atomic %) of carbon contained in the coating 22C to be calculated based on the C1s spectrum. This atomic concentration of carbon represents what atomic % the atomic concentration of carbon corresponds to, assuming that the sum of the atomic concentrations of all atoms present within the analysis range in the surface analysis of the coating 22C using XPS is 100 atomic %.

[0095] Furthermore, the atomic concentration (atomic %) of nitrogen contained in the coating 22C is calculated based on the N1s spectrum. This atomic concentration of nitrogen represents what atomic % the atomic concentration of nitrogen corresponds to when the sum of the atomic concentrations of all atoms present within the analysis range in the surface analysis of the coating 22C using XPS is taken as 100 atomic %.

[0096] Furthermore, the atomic concentration (atomic %) of lithium contained in the coating 22C is calculated based on the Li1s spectrum. This atomic concentration of lithium represents what atomic % the atomic concentration of lithium corresponds to, assuming that the sum of the atomic concentrations of all atoms present within the analysis range in the surface analysis of the coating 22C using XPS is 100 atomic %.

[0097] (Physical property condition 1) The concentration ratio X1, which is the first concentration ratio calculated by formula (1), is 0.4 to 2.7. This concentration ratio X1 is an index that indicates the relationship between the atomic concentration XC of carbon and the atomic concentration XN of nitrogen in the vicinity of the surface of the coating 22C, and indicates how the atomic concentration XC is relative to the atomic concentration XN. However, the values ​​of the atomic concentrations XC, XN and the concentration ratio X1 are each rounded off to one decimal place.

[0098] X1 = XC / XN (1) (X1 is the first concentration ratio. XC is the atomic concentration (atomic %) of carbon calculated based on the C1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.)

[0099] The concentration ratio X1 can be adjusted to fall within the above range (X1 = 0.4 to 2.7) by changing the mixing ratio of the negative electrode active material and the negative electrode binder. When the negative electrode active material layer 22B further contains a negative electrode conductor, the concentration ratio X1 can be adjusted to fall within the above range (X1 = 0.4 to 2.7) by changing the mixing ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductor.

[0100] (Physical property condition 2) The second concentration ratio, that is, the concentration ratio X2 calculated by formula (2) is 3.4 to 5.9. This concentration ratio X2 is an index showing the relationship between the atomic concentration XL of lithium and the atomic concentration XN of nitrogen in the vicinity of the surface of the coating 22C, and shows how the atomic concentration XL is relative to the atomic concentration XC. However, the values ​​of the atomic concentration XL and the concentration ratio X2 are each rounded off to one decimal place.

[0101] X2=XL / XN (2) (X2 is the second concentration ratio. XL is the atomic concentration (atomic %) of lithium calculated based on the Li1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.)

[0102] The concentration ratio X2 can be adjusted to be within the above range (X2=3.4 to 5.9) by changing the mixing ratio of the negative electrode active material and the negative electrode binder. When the negative electrode active material layer 22B further contains a negative electrode conductor, the concentration ratio X2 can be adjusted to be within the above range (X2=3.4 to 5.9) by changing the mixing ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductor.

[0103] (reason) The physical property conditions 1 and 2 are satisfied because, compared to a case in which the physical property conditions 1 and 2 are not satisfied, the physical properties of the coating 22C are optimized, and thus the distribution of carbon, nitrogen, and lithium in the vicinity of the surface of the negative electrode 22 is optimized. In this case, the input / output efficiency of lithium in the negative electrode active material layer 22B is improved while an increase in the internal resistance of the coating 22C is suppressed. As a result, the conductivity of the negative electrode 22 is ensured while the irreversible capacity caused by the consumption of lithium during charging and discharging is reduced, and lithium is smoothly and stably absorbed and released in the negative electrode 22. In particular, lithium is more likely to be smoothly and stably absorbed and released in the negative electrode 22 even when charging and discharging are repeated.

[0104] (Analysis and calculation procedures) The procedure for analyzing the negative electrode 22 using XPS and the procedure for calculating each of the concentration ratios X1 and X2 (including the procedure for calculating each of the atomic concentrations XC, XN, and XL) are as described below.

[0105] First, in order to put the secondary battery into a discharged state, the secondary battery is discharged until the battery voltage reaches 2.0 V. The current during discharging is not particularly limited and can be set arbitrarily.

[0106] Next, the secondary battery is disassembled to recover the negative electrode 22. Next, the negative electrode 22 is washed with an organic solvent such as dimethyl carbonate, and then dried. Next, the negative electrode 22 is cut into a rectangular shape (10 mm x 10 mm) to obtain a sample for analysis.

[0107] Next, the surface of the sample is analyzed using an XPS analyzer. In this case, a scanning X-ray photoelectron spectrometer PHI Quantera SXM manufactured by ULVAC-PHI, Inc. is used as the XPS analyzer. The analysis conditions are: light source = monochromatic Al Kα radiation (1486.6 eV), vacuum degree = 1×10 -9 Torr (=approx. 133.3×10 -9 Pa), analysis range (diameter) = 100 μm, analysis depth = 10 nm, and neutralization gun = yes.

[0108] This allows the surface (coating 22C) of the negative electrode 22 to be analyzed, thereby detecting the C1s spectrum, the N1s spectrum, and the Li1s spectrum. In addition, the atomic concentrations XC, XN, and XL (atomic %) are calculated using the calculation function of the XPS analyzer.

[0109] Here, when an XPS analyzer is used to detect the C1s spectrum, the N1s spectrum, and the Li1s spectrum and calculate the atomic concentrations XC, XN, and XL (atomic %), respectively, the processing described below is performed using the functions of the XPS analyzer.

[0110] First, when detecting each of the C1s spectrum, the N1s spectrum, and the Li1s spectrum, a so-called peak shift is performed. In this case, the positions of a series of spectra including the C1s spectrum, the N1s spectrum, and the Li1s spectrum are corrected so that the position (binding energy) of the peak top of the spectrum originating from lithium fluoride (Li-F) is 685.1 eV.

[0111] Secondly, when identifying each of the C1s spectrum, the N1s spectrum and the Li1s spectrum, so-called peak separation is carried out as necessary.

[0112] Specifically, when multiple peaks exist in the detection result of the C1s spectrum, a spectrum (C1s spectrum) having a peak top within the binding energy range of 282.0 eV to 283.6 eV is separated from the other spectra, thereby identifying the C1s spectrum used to calculate the atomic concentration XC.

[0113] In addition, when multiple peaks exist in the detection result of the N1s spectrum, the spectrum (N1s spectrum) having a peak top within the binding energy range of 394.5 eV to 405.0 eV is separated from the other spectra, thereby identifying the N1s spectrum used to calculate the atomic concentration XN.

[0114] Furthermore, when multiple peaks exist in the detection result of the Li1s spectrum, the spectrum (Li1s spectrum) having a peak top within the binding energy range of 50.0 eV to 61.5 eV is separated from the other spectra, thereby identifying the Li1s spectrum used to calculate the atomic concentration XL.

[0115] Third, when calculating each of the atomic concentrations XC, XN, and XL, the ranges (binding energy ranges) of the C1s spectrum, N1s spectrum, and Li1s spectrum used to calculate each of the atomic concentrations XC, XN, and XL are set.

[0116] Specifically, when calculating the atomic concentration XC, the range (binding energy range) of the C1s spectrum used to calculate the atomic concentration XC is set to 282.0 eV to 283.6 eV. When calculating the atomic concentration XN, the range (binding energy range) of the N1s spectrum used to calculate the atomic concentration XN is set to 394.5 eV to 405.0 eV. When calculating the atomic concentration XL, the range (binding energy range) of the Li1s spectrum used to calculate the atomic concentration XL is set to 50.0 eV to 61.5 eV.

[0117] Therefore, the concentration ratio X1 is calculated based on the atomic concentrations XC and XN, and the concentration ratio X2 is calculated based on the atomic concentrations XC and XL.

[0118] Finally, the above-mentioned calculation process of the concentration ratio X1 is repeated 20 times, and then the average value of the 20 concentration ratios X1 is calculated to obtain the final concentration ratio X1 (the concentration ratio X1 used to determine whether or not physical property condition 1 is satisfied).

[0119] In addition, the above-mentioned calculation process of the concentration ratio X2 is repeated 20 times, and then the average value of the 20 concentration ratios X2 is calculated to obtain the final concentration ratio X2 (the concentration ratio X2 used to determine whether or not physical property condition 2 is satisfied).

[0120] As a result, the concentration ratios X1 and X2 are each specified based on the results of the surface analysis of the negative electrode 22 using XPS.

[0121] When examining the physical properties of the negative electrode 22, that is, when examining whether the physical property conditions 1 and 2 are satisfied, it is preferable to perform a surface analysis of the non-facing portion R2 of the negative electrode 22, as shown in Fig. 3. As described above, the non-facing portion R2 is a portion that is not substantially involved in the charge / discharge reaction, and therefore the physical properties of the negative electrode 22 can be examined accurately with good reproducibility, regardless of the charge / discharge history (presence or absence of charge / discharge and the number of times, etc.).

[0122] <1-3. Operation> This secondary battery operates in the battery element 20 as follows.

[0123] During charging, lithium is released from the positive electrode 21 and is absorbed in the negative electrode 22 via the electrolyte. During discharging, lithium is released from the negative electrode 22 and is absorbed in the positive electrode 21 via the electrolyte. During discharging and charging, lithium is absorbed and released in an ionic state.

[0124] <1-4. Manufacturing method> When manufacturing a secondary battery, the secondary battery is assembled using the procedure described below as an example, and then a stabilization process is performed on the assembled secondary battery.

[0125] [Preparation of positive electrode] First, a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent are mixed together to prepare a positive electrode mixture. Then, the positive electrode mixture is put into a solvent to prepare a paste-like positive electrode mixture slurry. This solvent may be an aqueous solvent or an organic solvent. Then, the positive electrode mixture slurry is applied to both sides of the positive electrode collector 21A to form the positive electrode active material layer 21B. Finally, the positive electrode active material layer 21B is compression molded using a molding device such as a roll press. In this case, the positive electrode active material layer 21B may be heated, or the compression molding may be repeated multiple times. This produces a positive electrode 21 including the positive electrode collector 21A and the positive electrode active material layer 21B.

[0126] [Preparation of negative electrode] First, the negative electrode active material, the negative electrode binder containing the ternary copolymer, and the negative electrode conductive agent are mixed together to prepare a negative electrode mixture. Then, the negative electrode mixture is poured into a solvent to prepare a paste-like negative electrode mixture slurry. The details of the solvent are as described above.

[0127] Next, the negative electrode mixture slurry is applied to both sides of the negative electrode current collector 22A to form the negative electrode active material layer 22B. Next, the negative electrode active material layer 22B is compression molded using a molding device such as a roll press. Details regarding compression molding are as described above.

[0128] Finally, after assembling the secondary battery, a stabilization process is performed using the assembled secondary battery, which results in the formation of the coating 22C on the surface of the negative electrode active material layer 22B, thereby producing the negative electrode 22 including the negative electrode current collector 22A, the negative electrode active material layer 22B, and the coating 22C.

[0129] [Preparation of electrolyte] An electrolyte salt is added to a solvent, whereby the electrolyte salt is dispersed or dissolved in the solvent, and an electrolyte solution is prepared.

[0130] [Secondary battery assembly] First, the positive electrode lead 25 is connected to the positive electrode current collector 21A of the positive electrode 21 using a joining method such as welding, and the negative electrode lead 26 is connected to the negative electrode current collector 22A of the negative electrode 22 using a joining method such as welding.

[0131] Next, the positive electrode 21 and the negative electrode current collector 22A on which the negative electrode active material layer 22B is formed are stacked together with the separator 23 interposed therebetween to form a laminate (not shown). Next, the laminate is wound to produce a wound body (not shown) having a space 20S. This wound body has a similar configuration to that of the battery element 20, except that it does not include the coating 22C and is not impregnated with an electrolyte solution.

[0132] Next, with the wound body sandwiched between the insulating plates 12 and 13, the wound body and the insulating plates 12 and 13 are housed in the battery can 11. In this case, a positive electrode lead 25 is connected to the safety valve mechanism 15 using a joining method such as welding, and a negative electrode lead 26 is connected to the battery can 11 using a joining method such as welding. Next, an electrolyte is injected into the battery can 11, thereby impregnating the wound body with the electrolyte.

[0133] Finally, the battery cover 14 , the safety valve mechanism 15 and the PTC element 16 are housed in the battery can 11 , and then the battery can 11 is crimped via the gasket 17 .

[0134] As a result, the battery lid 14, the safety valve mechanism 15, and the PTC element 16 are fixed to the battery can 11, and the wound body is enclosed in the battery can 11, thereby assembling a secondary battery.

[0135] [Stabilization of secondary batteries after assembly] The assembled secondary battery is charged and discharged. Stabilization conditions such as the environmental temperature, the number of charge / discharge cycles (number of charge / discharge conditions), and the charge / discharge conditions can be set arbitrarily.

[0136] As a result, the coating 22C is formed on the surface of the negative electrode active material layer 22B, and the negative electrode 22 is produced. In this case, a coating having a similar configuration to that of the coating 22C may be formed on the surface of the positive electrode active material layer 21B. Thus, the battery element 20 is produced and is sealed in the battery can 11, and the secondary battery is completed.

[0137] <1-5. Actions and Effects> In this secondary battery, the negative electrode 22 includes a negative electrode active material layer 22B and a coating 22C, and the negative electrode active material layer 22B includes a negative electrode binder (ternary copolymer). In addition, in a surface analysis of the negative electrode 22 using XPS, the concentration ratio X1 is 0.4 to 2.7, and the concentration ratio X2 is 3.4 to 5.9.

[0138] In this case, as described above, the coating 22C is formed using a ternary copolymer, and thus the coating 22C is formed containing carbon, nitrogen, and lithium derived from the ternary copolymer as constituent elements. Furthermore, as described above, the physical property conditions 1 and 2 are satisfied, and thus the physical properties of the coating 22C are optimized, and thus the distributions of carbon, nitrogen, and lithium in the vicinity of the surface of the negative electrode 22 are optimized. This prevents an increase in the internal resistance of the coating 22C, and improves the input / output efficiency of lithium in the negative electrode active material layer 22B.

[0139] For these reasons, the irreversible capacity caused by the consumption of lithium during charging and discharging is reduced while the conductivity of the negative electrode 22 is ensured, and therefore lithium is smoothly and stably absorbed and released in the negative electrode 22 even if charging and discharging are repeated. Therefore, excellent battery characteristics can be obtained.

[0140] In particular, if the negative electrode active material layer 22B contains a negative electrode conductive agent and the negative electrode conductive agent contains a carbon material, not only is the conductivity of the negative electrode active material layer 22B improved, but the lithium absorption and release properties of the negative electrode active material layer 22B are also improved, thereby providing a greater effect.

[0141] Furthermore, if the secondary battery is a lithium ion secondary battery, a sufficient battery capacity can be stably obtained by utilizing the absorption and release of lithium, so that a higher effect can be obtained.

[0142] <2. Modifications> The configuration of the secondary battery can be modified as appropriate, as described below, although some of the modified examples described below may be combined with each other.

[0143] [Variation 1] A porous membrane separator 23 was used. However, although not specifically shown here, a laminated separator including a polymer compound layer may be used instead of the porous membrane separator 23.

[0144] Specifically, the laminated separator includes a porous film having a pair of surfaces and a polymer compound layer provided on one or both surfaces of the porous film. This is because the adhesiveness of the separator to each of the positive electrode 21 and the negative electrode 22 is improved, thereby suppressing the positional deviation of the battery element 20. This suppresses the deviation of the winding of each of the positive electrode 21, the negative electrode 22, and the separator, thereby suppressing the swelling of the secondary battery even if a decomposition reaction of the electrolyte occurs. The polymer compound layer includes polyvinylidene fluoride, etc. This is because polyvinylidene fluoride has excellent physical strength and is electrochemically stable.

[0145] One or both of the porous film and the polymer compound layer may contain one or more of a plurality of insulating particles. This is because the plurality of insulating particles dissipate heat when the secondary battery generates heat, improving the safety (heat resistance) of the secondary battery. The plurality of insulating particles contain one or more of insulating materials such as inorganic materials and resin materials. Specific examples of inorganic materials include aluminum oxide, aluminum nitride, boehmite, silicon oxide, titanium oxide, magnesium oxide, and zirconium oxide. Specific examples of resin materials include acrylic resin and styrene resin.

[0146] When a laminated separator is produced, a precursor solution containing a polymer compound and an organic solvent is prepared, and then the precursor solution is applied to one or both sides of a porous film. In this case, the precursor solution may contain a plurality of insulating particles.

[0147] Even when this laminated separator is used, the same effect can be obtained because lithium can move in an ionic state between the positive electrode 21 and the negative electrode 22. In this case, as described above, in particular, swelling of the secondary battery is further suppressed, and therefore a greater effect can be obtained.

[0148] [Variation 2] An electrolyte solution that is a liquid electrolyte is used, but an electrolyte layer that is a gel electrolyte may also be used, although this is not specifically shown.

[0149] In the battery element 20 using the electrolyte layer, the positive electrode 21 and the negative electrode 22 are wound facing each other with the separator 23 and the electrolyte layer interposed therebetween. The electrolyte layer is interposed between the positive electrode 21 and the separator 23, and is also interposed between the negative electrode 22 and the separator 23.

[0150] Specifically, the electrolyte layer contains a polymer compound together with an electrolyte solution, and the electrolyte solution is held by the polymer compound. This is because leakage of the electrolyte solution is prevented. The composition of the electrolyte solution is as described above. The polymer compound contains polyvinylidene fluoride and the like. When forming the electrolyte layer, a precursor solution containing an electrolyte solution, a polymer compound, a solvent, and the like is prepared, and then the precursor solution is applied to one or both sides of each of the positive electrode 21 and the negative electrode 22.

[0151] Even when this electrolyte layer is used, the same effect can be obtained because lithium ions can move between the positive electrode 21 and the negative electrode 22 via the electrolyte layer. In this case, leakage of the electrolyte is particularly prevented as described above, so that a higher effect can be obtained.

[0152] <3. Uses of secondary batteries> Finally, uses (application examples) of the secondary battery will be described.

[0153] The use of the secondary battery is not particularly limited. The secondary battery used as a power source may be a main power source or an auxiliary power source in electronic devices, electric vehicles, etc. The main power source is a power source that is used preferentially regardless of the presence or absence of other power sources. The auxiliary power source may be a power source used in place of the main power source or a power source that is switched from the main power source.

[0154] Specific examples of applications of secondary batteries are as follows: Electronic devices such as video cameras, digital still cameras, mobile phones, notebook computers, headphone stereos, portable radios, and portable information terminals; Storage devices such as backup power sources and memory cards; Power tools such as power drills and power saws; Battery packs mounted on electronic devices; Medical electronic devices such as pacemakers and hearing aids; Electric vehicles such as electric cars (including hybrid cars); Power storage systems such as home or industrial battery systems that store power in preparation for emergencies. In these applications, one secondary battery may be used, or multiple secondary batteries may be used.

[0155] The battery pack may include a single cell or a battery pack. The electric vehicle is a vehicle that runs on a secondary battery as a driving power source, and may be a hybrid vehicle that also includes a driving source other than the secondary battery. In the home power storage system, it is possible to use home electrical appliances and the like by utilizing the power stored in the secondary battery, which is a power storage source. EXAMPLES

[0156] An embodiment of the present technology will be described.

[0157] <Examples 1 to 3 and Comparative Examples 1 to 6> As described below, after the secondary batteries were manufactured, the battery characteristics of the secondary batteries were evaluated.

[0158] [Preparation of secondary battery] The cylindrical lithium ion secondary battery shown in FIGS. 1 to 3 was fabricated by the following procedure.

[0159] (Preparation of positive electrode) First, the positive electrode active material (lithium-containing compound (oxide) LiNi 0.82 Co 0.14 Al 0.04O2) 95.9 parts by mass, a positive electrode binder (polyvinylidene fluoride) 1.5 parts by mass, a positive electrode conductive agent (carbon black) 2.5 parts by mass, and an additive (polyvinylpyrrolidone) 0.1 parts by mass were mixed together to prepare a positive electrode mixture. Next, the positive electrode mixture was put into a solvent (N-methyl-2-pyrrolidone, an organic solvent), and the organic solvent was stirred to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to both sides of a positive electrode current collector 21A (a strip-shaped aluminum foil having a thickness of 15 μm) using a coating device, and then the positive electrode mixture slurry was dried to form a positive electrode active material layer 21B. Finally, the positive electrode active material layer 21B was compression-molded using a roll press machine. As a result, the positive electrode 21 was produced.

[0160] (Preparation of negative electrode) First, the negative electrode active material, the negative electrode binder (a ternary copolymer), and the negative electrode conductive agent (carbon black, which is a carbon material) were mixed together to prepare a negative electrode mixture.

[0161] The negative electrode active material was a mixture of graphite, which is a carbon material, and silicon oxide (SiO), which is a metal-based material, except that the metal-based material was silicon oxide whose surface was covered with a carbon material (graphite).

[0162] The copolymer of acrylamide, lithium acrylate, and acrylonitrile (AAALi) was used as the ternary copolymer, with the copolymerization amounts of acrylamide=18.6% by weight, lithium acrylate=36.2% by weight, and acrylonitrile=45.2% by weight.

[0163] In this case, as described later, the mixing ratios (mass ratios) of the negative electrode active material, the negative electrode binder, and the negative electrode conductor were adjusted to change each of the concentration ratios X1 and X2. Specifically, the mixing ratio of the negative electrode active material was adjusted to within a range of 95.0 parts by mass to 97.5 parts by mass, the mixing ratio of the negative electrode binder was adjusted to within a range of 1.7 parts by mass to 3.8 parts by mass, and the mixing ratio of the negative electrode conductor was adjusted to within a range of 0.8 parts by mass to 1.2 parts by mass.

[0164] The mixing ratio (mass ratio) of the carbon material and the metal-based material for the negative electrode active material was carbon material:metal-based material=14.4:1.

[0165] Next, the negative electrode mixture was added to a solvent (organic solvent N-methyl-2-pyrrolidone), and the organic solvent was stirred to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied to both sides of the negative electrode current collector 22A (strip-shaped copper foil with a thickness of 15 μm) using a coating device, and then the negative electrode mixture slurry was dried to form the negative electrode active material layer 22B. Next, the negative electrode active material layer 22B was compression-molded using a roll press machine.

[0166] Finally, as described later, a secondary battery was assembled, and then a stabilization treatment was performed using the assembled secondary battery, whereby a coating 22C was formed on the surface of the negative electrode active material layer 22B, and thus the negative electrode 22 was produced.

[0167] (Preparation of electrolyte) The electrolyte salts (lithium hexafluorophosphate and lithium tetrafluoroborate) were added to the solvent (ethylene carbonate, which is a cyclic carbonate ester, and diethyl carbonate, which is a chain carbonate ester), and the solvent was stirred to prepare the electrolyte solution.

[0168] In this case, the mixing ratio (weight ratio) of the solvents was ethylene carbonate:diethyl carbonate=13:59. The content of lithium hexafluorophosphate in the electrolyte was 18.5% by weight and the content of lithium tetrafluoroborate in the electrolyte was 0.7% by weight, so that the content of the electrolyte salt in the electrolyte was 19.2% by weight.

[0169] (Secondary battery assembly) First, the positive electrode lead 25 (aluminum foil) was welded to the positive electrode current collector 21A of the positive electrode 21, and the negative electrode lead 26 (copper foil) was welded to the negative electrode current collector 22A of the negative electrode 22.

[0170] Next, the positive electrode 21 and the negative electrode current collector 22A on which the negative electrode active material layer 22B was formed were laminated with a separator 23 (a microporous polyethylene film having a thickness of 12 μm) interposed therebetween to produce a laminate. Next, the laminate was wound to produce a wound body having a space 20S, and then a center pin 24 was inserted into the space 20S.

[0171] Next, the insulating plates 12 and 13 were housed together with the wound body in the battery can 11. In this case, the positive electrode lead 25 was welded to the safety valve mechanism 15, and the negative electrode lead 26 was welded to the battery can 11. Next, an electrolyte was injected into the inside of the battery can 11, thereby impregnating the wound body with the electrolyte.

[0172] Finally, the battery cover 14 , the safety valve mechanism 15 and the PTC element 16 were housed in the battery can 11 , and then the battery can 11 was crimped via the gasket 17 .

[0173] Thus, the wound body was enclosed in the battery can 11, and a secondary battery was assembled.

[0174] (Stabilization of secondary batteries after assembly) The assembled secondary battery was charged and discharged for one cycle in a room temperature environment (temperature = 23°C), and then left in the same environment (aging time = 60 hours). During charging, the battery was charged at a constant current of 0.1C until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.05C. During discharging, the battery was discharged at a constant current of 0.1C until the voltage reached 2.5V. 0.1C is the current value at which the battery capacity (theoretical capacity) is fully discharged in 10 hours, and 0.05C is the current value at which the battery capacity is fully discharged in 20 hours.

[0175] As a result, a coating 22C was formed on the surface of the negative electrode active material layer 22B, thereby producing a negative electrode 22. Thus, an electrochemically stabilized battery element 20 was produced, and the battery element 20 was sealed in the battery can 11, thereby completing a secondary battery (Examples 1 to 3 and Comparative Examples 1 to 4).

[0176] [Production of other secondary batteries] For comparison, other secondary batteries were fabricated in the same manner except that other copolymers were used as the negative electrode binder instead of the ternary copolymer.

[0177] As another copolymer, a copolymer of acrylamide, acrylic acid, and acrylonitrile (AAA) was used, in which the copolymerization amount of acrylamide was 18.6% by weight, the copolymerization amount of acrylic acid was 36.2% by weight, and the copolymerization amount of acrylonitrile was 45.2% by weight (Comparative Example 5).

[0178] As another copolymer, a copolymer of acrylamide, sodium acrylate, and acrylonitrile (AAANa) was used, in which the copolymerization amount of acrylamide was 18.6% by weight, the copolymerization amount of sodium acrylate was 36.2% by weight, and the copolymerization amount of acrylonitrile was 45.2% by weight (Comparative Example 6).

[0179] [Concentration ratio X1,X2] After the secondary battery was completed, the surface of the negative electrode 22 was analyzed using XPS to calculate the concentration ratios X1 and X2, and the results are shown in Table 1. The analysis procedure for the negative electrode 22 using XPS and the calculation procedure for the concentration ratios X1 and X2 were as described above.

[0180] When preparing a secondary battery, as described above, in the process of preparing the negative electrode 22, the concentration ratios X1 and X2 were each changed by adjusting the mixing ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent.

[0181] [Evaluation of battery characteristics] The battery characteristics (electrical resistance characteristics, initial charge / discharge characteristics, discharge temperature characteristics, and cycle characteristics) were evaluated according to the procedures described below, and the results shown in Table 1 were obtained.

[0182] (Electrical resistance characteristics) The secondary battery was charged in a room temperature environment (temperature = 23°C). During charging, it was charged at a constant current of 1C until the voltage reached 3.6V, and then it was charged at a constant voltage of 3.6V until the total charging time reached 10 hours. 1C is the current value that fully discharges the battery capacity in 1 hour.

[0183] Thereafter, the electrical resistance (mΩ), which is an index for evaluating the electrical resistance characteristics, was measured using an AC impedance method (frequency = 1 kHz).

[0184] (Initial charge / discharge characteristics) First, the secondary battery was charged in a room temperature environment (temperature = 23 ° C.) to measure the charge capacity. Next, the secondary battery was discharged in the same environment to measure the discharge capacity. Finally, the initial efficiency, which is an index for evaluating the initial charge and discharge characteristics, was calculated based on the formula: initial efficiency (%) = (discharge capacity / charge capacity) × 100.

[0185] During charging, the battery was charged at a constant current of 0.2 C until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the total charging time reached 10 hours. During discharging, the battery was discharged at a constant current of 0.2 C until the voltage reached 2.0 V. 0.2 C is the current value that fully discharges the battery capacity in 5 hours.

[0186] (Discharge temperature characteristics) First, the secondary battery was charged in a room temperature environment (temperature = 23 ° C.) During charging, it was charged at a constant current of 1 C until the voltage reached 4.2 V, and then it was charged at a constant voltage of 4.2 V until the total charging time reached 2.5 hours.

[0187] Next, the secondary battery was discharged in six different environments (temperatures: -20°C, -10°C, 0°C, 23°C, 45°C, 60°C) to measure six different discharge capacities. During discharge, the battery was discharged at a constant current of 2.5C until the voltage reached 2.5V. 2.5C is the current value at which the battery capacity is fully discharged in 0.4 hours.

[0188] As a result, six types of discharge capacity were obtained in each of Examples 1 to 3 and Comparative Examples 1 to 6.

[0189] Subsequently, a subtraction process was performed in which the six types of discharge capacities obtained in Comparative Example 6 were subtracted from the six types of discharge capacities obtained in Example 1 to obtain six types of discharge capacities after the subtraction process.

[0190] In this case, the subtraction process was performed for each of the six types of temperatures (=-20°C, -10°C, 0°C, 23°C, 45°C, 60°C) described above, thereby performing six types of subtraction process described below. First, the subtraction process was performed using the calculation formula of discharge capacity of Example 1 (temperature = -20°C) - discharge capacity of Comparative Example 6 (temperature = -20°C). Second, the subtraction process was performed using the calculation formula of discharge capacity of Example 1 (temperature = -10°C) - discharge capacity of Comparative Example 6 (temperature = -10°C). Third, the subtraction process was performed using the calculation formula of discharge capacity of Example 1 (temperature = 0°C) - discharge capacity of Comparative Example 6 (temperature = 0°C). Fourth, the subtraction process was performed using the calculation formula of discharge capacity of Example 1 (temperature = 23°C) - discharge capacity of Comparative Example 6 (temperature = 23°C). Fifth, the subtraction process was performed using the calculation formula of discharge capacity of Example 1 (temperature = 45°C) - discharge capacity of Comparative Example 6 (temperature = 45°C). Sixth, a subtraction process was performed using the formula: discharge capacity of Example 1 (temperature=60° C.)−discharge capacity of Comparative Example 6 (temperature=60° C.).

[0191] Next, the ratios of the six types of discharge capacities after the subtraction process to the six types of discharge capacities obtained in Comparative Example 6 were calculated to obtain six types of improvement rates (%).

[0192] In this case, the calculation process of the ratio was performed for each of the six types of temperatures (=-20°C, -10°C, 0°C, 23°C, 45°C, 60°C) described above, thereby performing the calculation process of six types of improvement rates described below. Specifically, first, the improvement rate was calculated using the calculation formula: improvement rate = [discharge capacity after subtraction process (temperature = -20°C) / discharge capacity of Comparative Example 6 (temperature = -20°C)] x 100. Second, the improvement rate was calculated using the calculation formula: improvement rate = [discharge capacity after subtraction process (temperature = -10°C) / discharge capacity of Comparative Example 6 (temperature = -10°C)] x 100. Third, the improvement rate was calculated using the calculation formula: improvement rate = [discharge capacity after subtraction process (temperature = 0°C) / discharge capacity of Comparative Example 6 (temperature = 0°C)] x 100. Fourth, the improvement rate was calculated using the formula: improvement rate = [discharge capacity after subtraction (temperature = 23 ° C) / discharge capacity of Comparative Example 6 (temperature = 23 ° C)] × 100. Fifth, the improvement rate was calculated using the formula: improvement rate = [discharge capacity after subtraction (temperature = 45 ° C) / discharge capacity of Comparative Example 6 (temperature = 45 ° C)] × 100. Sixth, the improvement rate was calculated using the formula: improvement rate = [discharge capacity after subtraction (temperature = 60 ° C) / discharge capacity of Comparative Example 6 (temperature = 60 ° C)] × 100.

[0193] Next, the average value of the six types of improvement rates was calculated to calculate the average improvement rate (%), which is an index for evaluating the discharge temperature characteristics.

[0194] Finally, the average improvement rates were calculated for each of Examples 2 and 3 and Comparative Examples 1 to 5 using the same procedure as that used for calculating the average improvement rate for Example 1.

[0195] (Cycle characteristics) First, the discharge capacity (discharge capacity at the first cycle) was measured by charging and discharging the secondary battery in a room temperature environment (temperature = 23 ° C.). Next, the discharge capacity (discharge capacity at the 650th cycle) was measured by repeatedly charging and discharging the secondary battery in the same environment until the total number of cycles reached 650 cycles. Finally, the capacity retention rate, which is an index for evaluating cycle characteristics, was calculated based on the formula: Capacity retention rate (%) = (Discharge capacity at the 650th cycle / Discharge capacity at the first cycle) x 100. The charge and discharge conditions were the same as those used to evaluate the initial charge and discharge characteristics.

[0196] [Table 1]

[0197] [Consideration] As shown in Table 1, the electrical resistance, initial efficiency, average improvement rate, and capacity retention rate each varied greatly depending on the configuration of the secondary battery.

[0198] In detail, when the negative electrode binder did not contain a ternary copolymer but contained other copolymers (Comparative Examples 5 and 6), the electrical resistance increased and the initial efficiency, average improvement rate, and capacity retention rate each decreased regardless of whether the physical property conditions 1 and 2 (concentration ratio X1 = 0.4 to 2.7 and concentration ratio X2 = 3.4 to 5.9) were satisfied.

[0199] In contrast, when the negative electrode binder contained a ternary copolymer (Examples 1 to 3 and Comparative Examples 1 to 4), the electrical resistance, initial efficiency, average improvement rate, and capacity retention rate each varied depending on whether the physical property conditions 1 and 2 were satisfied.

[0200] Specifically, when the physical property conditions 1 and 2 were not satisfied (Comparative Examples 1 to 4), the electrical resistance increased, and the initial efficiency, average improvement rate, and capacity retention rate each decreased.

[0201] However, when the physical property conditions 1 and 2 were satisfied (Examples 1 to 3), the electrical resistance decreased, and the initial efficiency, average improvement rate, and capacity retention rate each increased.

[0202] In particular, when the physical property conditions 1 and 2 were satisfied, when the negative electrode active material layer 22B contained a negative electrode conductive agent (carbon material), the electrical resistance was sufficiently reduced, and the initial efficiency, the average improvement rate, and the capacity retention rate were each sufficiently increased.

[0203] [summary] From the results shown in Table 1, when the negative electrode 22 includes the negative electrode active material layer 22B and the coating 22C, the negative electrode active material layer 22B includes a negative electrode binder (ternary copolymer), and the concentration ratio X1 is 0.4 to 2.7 and the concentration ratio X2 is 3.4 to 5.9 in the surface analysis of the negative electrode 22 using XPS, the initial efficiency, average improvement rate, and capacity retention rate each increase while the electrical resistance decreases. Therefore, the electrical resistance characteristics, initial charge / discharge characteristics, discharge temperature characteristics, and cycle characteristics are each improved, and therefore excellent battery characteristics are obtained in the secondary battery.

[0204] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the present technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.

[0205] Specifically, the secondary battery has been described as having a cylindrical battery structure. However, the battery structure of the secondary battery is not particularly limited, and may be a laminate film type, a square type, a coin type, a button type, or the like.

[0206] Although the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, the electrode reactant may be other alkali metals such as sodium and potassium, as described above, or alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.

[0207] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.

[0208] The present technology can also be configured as follows. <1> A positive electrode, a negative electrode, and an electrolyte solution are provided, The negative electrode is a negative electrode active material layer including a negative electrode binder; a coating provided on the surface of the negative electrode active material layer; Including, The negative electrode binder contains a copolymer of acrylamide, lithium acrylate, and acrylonitrile, A C1s spectrum, an N1s spectrum and an Li1s spectrum were detected by surface analysis of the negative electrode using X-ray photoelectron spectroscopy. the first concentration ratio calculated by the formula (1) is equal to or greater than 0.4 and equal to or less than 2.7, The second concentration ratio calculated by the formula (2) is equal to or greater than 3.4 and equal to or less than 5.9. Secondary battery. X1 = XC / XN (1) (X1 is the first concentration ratio. XC is the atomic concentration (atomic %) of carbon calculated based on the C1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.) X2=XL / XN (2) (X2 is the second concentration ratio. XL is the atomic concentration (atomic %) of lithium calculated based on the Li1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.) <2> The negative electrode active material layer further contains a negative electrode conductive agent, The negative electrode conductive agent contains a carbon material. <1> The secondary battery according to claim 1. <3> It is a lithium-ion secondary battery. <1> or <2> The secondary battery according to claim 1. [Explanation of symbols]

[0209] 21...Positive electrode, 22...Negative electrode, 22B...Negative electrode active material layer, 22C...Coating.

Claims

1. A positive electrode, a negative electrode, and an electrolyte solution are provided, The negative electrode is a negative electrode active material layer including a negative electrode binder; a coating provided on the surface of the negative electrode active material layer; Including, The negative electrode binder contains a copolymer of acrylamide, lithium acrylate, and acrylonitrile, A C1s spectrum, an N1s spectrum and an Li1s spectrum were detected by surface analysis of the negative electrode using X-ray photoelectron spectroscopy; the first concentration ratio calculated by the formula (1) is equal to or greater than 0.4 and equal to or less than 2.7, The second concentration ratio calculated by the formula (2) is equal to or greater than 3.4 and equal to or less than 5.

9. Secondary battery. X1=XC / XN...(1) (X1 is the first concentration ratio. XC is the atomic concentration (atomic %) of carbon calculated based on the C1s spectrum. XN is the atomic concentration (atomic %) of nitrogen calculated based on the N1s spectrum.) X2=XL / XN...(2) (X2 is the second concentration ratio. XL is the atomic concentration of lithium (atomic %) calculated based on the Li1s spectrum. XN is the atomic concentration of nitrogen (atomic %) calculated based on the N1s spectrum.)

2. The negative electrode active material layer further contains a negative electrode conductive agent, The negative electrode conductive agent contains a carbon material. The secondary battery according to claim 1 .

3. It is a lithium-ion secondary battery. The secondary battery according to claim 1 or 2.

Citation Information

Patent Citations

  • Water-soluble adhesive for lithium ion battery, preparation method for water-soluble adhesive, electrode sheet and battery

    CN111139002A

  • Lithium secondary battery anode and lithium secondary battery using it

    JP2005203370A

  • Anode and lithium cell adopting above

    JP2007080827A

  • Negative electrode and battery, and these manufacturing method

    JP2009037842A

  • Nonaqueous lithium power storage device

    JP2017195231A